Short term effects of contralateral tendon vibration on motor unit discharge rate variability and force steadiness in people with Parkinson’s disease - Kim, Changki; Wile, Daryl J.; Kraeutner, Sarah N.; Larocque, Kaylee A.; Jakobi, Jennifer M. (Frontiers in Aging Neuroscience, 2024)
BACKGROUND: Vibration of one limb affects motor performance of the contralateral limb, and this may have clinical implications for people with lateralized motor impairments through vibration-induced increase in cortical activation, descending neural drive, or spinal excitability. OBJECTIVE: The objective of this study was to evaluate the effects of acute biceps brachii tendon vibration on force steadiness and motor unit activity in the contralateral limb of persons with Parkinson's disease. METHODS: Ten participants with mild to moderate Parkinson's disease severity performed a ramp, hold and de-ramp isometric elbow flexion at 5% of maximum voluntary contraction with the more-affected arm while vibration was applied to the distal biceps brachii tendon on the contralateral, less-affected arm. Using intramuscular fine wire electrodes, 33 MUs in the biceps brachii were recorded across three conditions (baseline, vibration, and post-vibration). Motor unit recruitment & derecruitment thresholds, discharge rates & variability, and elbow flexion force steadiness were compared between conditions with and without vibration.RESULTS: Coefficient of variation of force and discharge rate variability decreased 37% and 17%, respectively in post-vibration compared with baseline and vibration conditions. Although the motor unit discharge rates did not differ between conditions the total number of motor units active at rest after de-ramp were fewer in the post-vibration condition.CONCLUSIONS: Contralateral tendon vibration reduces MU discharge rate variability and enhances force control on the more affected side in persons with Parkinson's disease.